Web-Based Assignment Information System Serves to Improve Economic Research at Universities and Public Services - Susanto, Meitio; Johan, Monika Evelin; Sulaiman, Agus; Fianty, Melissa Indah (SAFE-Network, 2024)
Community Outreach is one of the Tridharma of Higher Education which is the obligation of lecturers in Indonesia. The Institute for Research and Community Outreach (LPPM) at Universitas Multimedia Nusantara (UMN) is an institution that supports and facilitates Community Outreach activities, starting from submitting proposals, monitoring implementation, assignment letters, and completion reports. There are several procedures such as filling in data on a form which can be accessed using the Linktree link. This makes it difficult for LPPM admins to manually recap data by checking the forms that have been submitted. Even though there is a Research and Community Outreach (RCOS) website, there is no feature for Community Outreach services yet. This research develops the RCOS LPPM website at UMN by adding features for Community Outreach services. By using the Agile development method which focuses on developers, existing software, customers, and change requirements, the web-based information system created is expected to further complement the digitalization and automation of LPPM UMN service features, making it easier for both lecturers and admins in the process.